2013
DOI: 10.1089/ars.2012.4714
|View full text |Cite
|
Sign up to set email alerts
|

Human and Methodological Sources of Variability in the Measurement of Urinary 8-Oxo-7,8-dihydro-2′-deoxyguanosine

Abstract: Aims: Urinary 8-oxo-7,8-dihydro-2¢-deoxyguanosine (8-oxodG) is a widely used biomarker of oxidative stress. However, variability between chromatographic and ELISA methods hampers interpretation of data, and this variability may increase should urine composition differ between individuals, leading to assay interference. Furthermore, optimal urine sampling conditions are not well defined. We performed inter-laboratory comparisons of 8-oxodG measurement between mass spectrometric-, electrochemical-and ELISA-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 31 publications
4
107
2
Order By: Relevance
“…A larger case-control study with 1,066 cases and a prospective study with 350 cases split in pre-and postmenopausal cancer found no association between 8-oxodG excretion and breast cancer risk in logistic regression analysis (19)(20)(21). Nevertheless, these studies used ELISA-based measurement of 8-oxodG, which show substantially less precision, accuracy, and ability to discriminate patients and healthy subjects compared with the chromatographic assays (17,18). This could increase measurement error in exposure assessment biasing risk toward null.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A larger case-control study with 1,066 cases and a prospective study with 350 cases split in pre-and postmenopausal cancer found no association between 8-oxodG excretion and breast cancer risk in logistic regression analysis (19)(20)(21). Nevertheless, these studies used ELISA-based measurement of 8-oxodG, which show substantially less precision, accuracy, and ability to discriminate patients and healthy subjects compared with the chromatographic assays (17,18). This could increase measurement error in exposure assessment biasing risk toward null.…”
Section: Discussionmentioning
confidence: 99%
“…However, only one spot sample of urine was collected at enrolment and this may not be representative for the long period at risk. (18,49,50). The concentrations of 8-oxodG had to be adjusted by creatinine concentration (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative stress markers such as MDA can be influenced by numerous factors including physical, chemical, and biological parameters, hence certain extent of within-individual variation is inevitable. For example, urinary 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG), another widely used biomarker of oxidative stress, showed a within-individual variation of 20% CV in the first morning void samples collected from 26 healthy nonsmoking adults (Barregard et al, 2013). While quantitative explanation is not possible, day-of-the-week variation of stress biomarkers may also contribute to the observation of the present study, e.g., the 1st set of samples were collected on Tuesday (Day 2) morning following weekend vs. the 2nd set of samples were collected on Friday (Day 5).…”
Section: Association With Oxidative Stress Biomarker In Urinementioning
confidence: 99%